Evaluation of maternal and perinatal morbidity and mortality in eclampsia by early termination of pregnancy - Mondal, Suresh C.; Lahiri, Sandip (International Journal of Research in Medical Sciences, 2020)
Background: Eclampsia is one of the leading causes of maternal mortality in India. Methods: A prospective observational study was done on 200 pregnant women admitted with antepartum eclampsia in Malda Medical College from 1 April 2017 to 30 October 2019. Group A included patients who delivered through vaginal route within 10 to 12 hrs of eclampsia by stabilisation of patients while Group B included subjects who underwent early caesarean section for uncontrolled convulsions or poor Bishop score. Maternal and perinatal outcomes were compared between the groups. Data was recorded in a pretested performa and was analyzed using appropriate statistical methods with SPSS. Results: Caesarean section (group B) was done in 130 cases (65%) while vaginal delivery (group A) was done in 65 cases (37.5%). Group A had higher maternal mortality (10.7%) in comparison to group B (4.6%) which was statistically not significant (p=0.1075). There were 32 neonatal deaths (24.6%) and 11 still births (8.46%) in group A while there were 12 neonatal deaths (18.46%) and 3 still births (4.61%) in group B. There was a statistically significant difference (p<0.0001) between the groups with respect to total perinatal deaths. Conclusions: Antenatal and intranatal eclampsia should be managed by early termination of pregnancy preferably with Caesarean section. Early presentation and timely decision to terminate pregnancy will improve the maternal and perinatal outcome.